IHI ID 17 Improving timely recognition of sepsis in pediatric intensive care unit patients. (December 2018) - Vidrine, Rhea; Zackoff, Matthew; Pfeiffer, Stephen; Paff, Zachary; Seger, Brandy; Walden, Jessica; Schnieder, Carrie; Stumpf, Taryn; Smith, Cecilia; Stalets, Erika; Dewan, Maya
Abstract : Background: Sepsis is a leading cause of pediatric mortality. Prior research shows that patients who receive antibiotics within 6 hours of sepsis recognition have decreased in-hospital mortality. While we had demonstrated improvements in recognition of sepsis for newly admitted patients, delayed recognition of sepsis in the pediatric ICU (PICU) remains a significant vulnerability. Objectives: To increase and sustain the days between delayed severe sepsis recognition in the PICU by 50% within two years. Methods: Using the Improving Pediatric Sepsis Outcomes database from January 1, 2016 to July 31, 2018 we identified episodes of delayed recognition of severe sepsis in patients admitted to the PICU. We define delayed severe sepsis recognition as time to antibiotics 6 hours after obtaining blood cultures. We utilized several PDSA cycles to improve the sepsis identification process within our unit including use of multi-disciplinary sepsis huddles for high risk patients and an automated clinical decision support (CDS) tool (figure 1 and 2 ). The primary outcome of delayed sepsis recognition was tracked using a days-between t-chart. Results: After implementation of sepsis huddles in May 2017, the days between episodes of delayed severe sepsis recognition improved from our baseline of 9 days to 28 days. Since the implementation of our automated CDS sepsis screening tool in May 2018, we have shown sustained improvement (figure 3 ). Conclusions: Implementation of a sepsis huddles and an automated CDS tool in the PICU has led to an improvement in the days between cases of delayed severe sepsis recognition.